PEMIKIRAN HUKUM ISLAM KLASIK DAN MODERN: KARAKTERISTIK, METODE, PENGEMBANGAN, DAN KEBERLAKUANNYA - Didi Kusnadi (Asy-Syari'ah, 2014)
Syekh Mahmûd Syaltût stated that Islamic law is a universal legal system that made it lives and thrives in society. Islamic law is an independent legal system, not taken from other laws, so it has own character. The sources of Islamic law are derived from the Koran, Sunna, and ijtihâd. The truth of ijtihâd is relative and dzanni, but it will be received by us if it is not contradicted to the Sharia or sacred texts. Thus, It makes a difference opinion among the scholars in the process of ijtihâd on how to formulate Islamic law (istinbâth al-ahkâm) which is caused by three things: First, the formulation of rules (al-tahsîs). There are scholars who hold to the understanding uslub or dalil syara’ and some scholars adhered to the issues of branches (furu‘); Second, the methodology (manhaj) or the formulation of the legal methods that used, both inductive and deductive; Third, aspects of thinking which is the fundamental basis of the scholars that used in ijtihâd. Development and validity of ijtihâd will always still be opened and dynamic, which is following the development of human thought and the dynamics of Islamic law.